2010
DOI: 10.1590/s1415-47572010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Change in genetic size of small-closed populations: lessons from a domestic mammal population

Abstract: The aim of this study was to monitor changes in genetic size of a small-closed population of Iranian Zandi sheep, by using pedigree information from animals born between 1991 and 2005. The genetic size was assessed by using measures based on the probability of identity-by-descend of genes (coancestry, f, and effective population size, Ne ), as well as measures based on probability of gene origin (effective number of founders, fe , effective number of founder genomes, fg , and effective number of non-founder ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Among all groups in this study, the observed heterozygosity, expected heterozygosity, and pi of CRS were 0.387, 0.375, 0.000043, respectively, which were at the relatively high level of genomic diversity among the 16 cattle populations in this study. One reason may be that CRS was crossed with local breeds, which is consistent with previous research [54]. On the other hand, the bovine SNP chips were optimized for use in taurine, which has a little bias and is not suitable for studying the genetic diversity and origin of domestic cattle in other regions [55].…”
Section: Discussionsupporting
confidence: 65%
“…Among all groups in this study, the observed heterozygosity, expected heterozygosity, and pi of CRS were 0.387, 0.375, 0.000043, respectively, which were at the relatively high level of genomic diversity among the 16 cattle populations in this study. One reason may be that CRS was crossed with local breeds, which is consistent with previous research [54]. On the other hand, the bovine SNP chips were optimized for use in taurine, which has a little bias and is not suitable for studying the genetic diversity and origin of domestic cattle in other regions [55].…”
Section: Discussionsupporting
confidence: 65%
“…The value of f ge represents the cumulative loss of genetic diversity since the base population and directly relates to N e [18,19]. Ratios of the above mentioned parameters of gene origin have been used to interpret the loss in genetic diversity by several authors [23,24,30], but definition and interpretation of the parameter ratios have been diverse and non-quantifiable (in absolute sense).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that hybridization of the Taurine and Indicine breeds conferred a higher genetic diversity of the Simbra breed in comparison with the purebred breeds (Ghafouri-Kesbi, 2010;Zhang et al, 2015). This was obvious from the negative inbreeding coefficient (f ) estimate that indicated an excess of heterozygosity even beyond what is expected under Hardy-Weinberg equilibrium in the Simbra population (Maiorano et al, 2018).…”
Section: Discussionmentioning
confidence: 70%